Effect of thinning of vegetative shoots on cut flower production of 'Serena' alstroemeria (Alstroel1zeria Izybrids) under polyhonse conditions* - SINGH, MK; RAM, R; PRASAD, R (The Indian Journal of Agricultural Sciences, 2011)
Investigation was conducted on l-year-old plants of I.Serena' alstroemeria on production of cut flowers under polyhouse conditions by thinning 0, 30, 60 and 90% of vegetative shoots on monthly basis during flower production period (March - July). The maximum plant / year offlowering stenlS and length of flowering stem were observed 75 and 91.37 em respectively by 30% thinning of vegetative shoots followed by 60% thinning (61.50 and 87.50 enl respectively). Thinning 30% gave better response for'A' grade number of flowering steIns (38)/plant followed by 60, 90% thinning and without thinning or'vegetative shoots (34,32 and 24 respectively).